Analysis of the electromagnetic field (EMF) distribution on the human body due to earth’s potential rise (EPR) of different types of soil - Bani Hashim, Siti Nurhidayu; Nik Ali, N. H.; Abd Rahman, M. S.; Johari, D.; Abdul Haris, Faranadia; Ab Kadir, M. Z. A. (IEEE, 2023)
This paper investigates the magnetostatic properties of Earth’s Potential Rise (EPR) distribution caused by a direct lightning strike on the ground, taking into account the specific characteristics of different parts of the human body. The study includes various soil parameters and considers different distances between objects and striking points. To simulate these conditions, a designed model was used in conjunction with finite element software (ANSYS). The simulation results show that lightning striking the soil can significantly increase the current potential around the attachment point, extending to distant parts of the earth due to soil conductivity. To evaluate the potential impact on the human body, the study analyzed the values of the Electromagnetic Field (EMF) and EPR distributions, which can cause injuries or fatalities. Understanding these effects is crucial for developing effective grounding and lightning protection systems. Public safety measures should also be disseminated to reduce the risks posed to humanity. The results of the analysis demonstrate that different soil factors influence the human body in distinct ways. This information can be used to develop more effective safety measures and improve the protection of human life from lightning strikes.